Kajian Sosio-Teologis terhadap Fenomena Ketangguhan Perempuan Penenun Ulos di Desa Siraja Hutagalung (Jurnal Pendidikan Agama dan Teologi, 2025)
Women in traditional societies often face complex challenges, particularly within patriarchal social systems. In Batak Toba culture, women are frequently placed in subordinate positions and regarded merely as complements within the household. However, social realities reveal a different dynamic, where women are able to emerge as key actors in sustaining family economies while also preserving cultural identity. This study aims to examine the resilience of female ulos weavers in Siraja Hutagalung Village from a socio-theological perspective. The method used is qualitative with a descriptive approach. Primary data were obtained through in-depth interviews with five main informants who work as ulos weavers, while secondary data came from literature studies related to women’s resilience issues. The analysis refers to resilience theory and gender role theory. The findings show that female ulos weavers hold a central role in family life. Their weaving is not only a cultural product but also symbolizes spiritual strength, loyalty, and independence. Thus, women’s resilience is not merely a social reality but also a tangible expression of spirituality embedded in daily life.